Purpurin, a anthraquinone induces ROS-mediated A549 lung cancer cell apoptosis via inhibition of PI3K/AKT and proliferation. (20th April 2021) - Bo, Su; Lai, Jing; Lin, Honyu; Luo, Xue; Zeng, Yiqiong; Du, Tianying
Abstract: Objectives: In this study, we sought to evaluate purpurin, a natural biomedicine and a potential inhibitor in decreasing the growth rate of lung cancer cells by modulating the role of PI3K/AKT signalling-associated proliferation and apoptosis. Methods: A549 cells were treated with purpurin (30 μM) for 24 and 48 h incubation, respectively, and it has been analysed for cytotoxicity, ROS-mediated apoptotic staining. Moreover, purpurin-mediated lipid peroxidation and GSH were measured by biochemical estimation. Furthermore, PI3K/AKT signalling-mediated cell proliferation and apoptotic gene expression done were by western blot. Key findings: In this study, we observed that purpurin could effectively kill A549 cancer cell lines and leads to cell death, thus conforming increased cytotoxicity, production of ROS-mediated enhancement of lipid peroxidation, nuclear fragmentation and apoptosis. Moreover, the GSH content of A549 cell lines was also diminished after treatment with purpurin. This study demonstrates that purpurin inhibits the phosphorylated PI3K/AKT molecules mediated cyclin-D1 and PCNA, thereby inducing apoptosis by observing increased proapoptotic mediators Bax, cleaved PARP, cytochrome-c, caspase-9 and caspase-3; and decreased Bcl-2 expression in the lung cancer cell lines. Conclusion: This result concluded that purpurin eliminates the A549 lung cancer cells by blocking the PI3K/AKT pathway thereby inducing apoptosis.